The Right Family - Ben-Asher, Noa; Pollans, Margot J. (Columbia Journal of Gender and Law, 2020)
The family plays a starring role in American law. Families, the law tells us, are special. They merit many state and federal benefits, including tax deductions, testimonial privileges, untaxed inheritance, and parental presumptions. Over the course of the twentieth century, the Supreme Court expanded individual rights stemming from familial relationships. In this Article, we argue that the concept of family in American law matters just as much when it is ignored as when it is featured. We contrast policies in which the family is the key unit of analysis with others in which it is not. Looking at four seemingly disparate areas of recent policymaking—the travel ban, family separation at the southern border, agricultural subsidies, and the religious rights of closely held corporations—we explore the interplay between the family, the individual, and the corporation in modern law. We observe that both liberals and conservatives make use of the family to humanize or empower certain people, and both reject the family when seeking to dehumanize or disempower. Where liberals and conservatives differ is which families they choose to champion. Ultimately, we conclude that the use of family as a mechanism through which to confer rights and benefits is a cover to hide policies that entrench and exacerbate existing racial and religious hierarchies. Further, in the context of family businesses, it risks becoming a steppingstone for radical expansion of rights to businesses themselves. To tell this story, we analyze the use and rhetoric of family in politics, media, and recent Supreme Court decisions such as Trump v. Hawaii (2018), Burwell v. Hobby Lobby (2014), Kerry v. Din (2015), and Masterpiece Cakeshop v. Colorado Civil Rights Commission (2018).